Assessment of purine catabolism and morbidity in miners depending on their work experience - Diana M. Shaukhat; Lyazat K. Ibrayeva; Dina Kh. Rybalkina; Irina V. Bacheva; Igor V. Bukhtiyarov; Aigul U. Amanbekova; Tleуuzhan O. Abugalieva (Russian Open Medical Journal)
Objective — The role of end products of purine metabolism as predictors of the development of pathological changes and diseases caused by the impact of dust on the human body in a professional environment vs. the work experience (duration of underground experience in the field). Material and Methods — We analyzed the content of the end products of purine metabolism in the blood plasma of coal miners depending on the length of working in dusty conditions and evaluated the morbidity in the studied individuals via an analysis of the biomarkers. Results — The median levels of xanthine and uric acid exhibited similar significant trends with a decrease in values with underground work experience under 3 years and an increase in values with 5 or more years of experience. When assessing outcomes 1-3 years after the selection of coal miners into the study, we revealed that both acute diseases (acute respiratory viral infection (ARVI), COVID-19, acute bronchitis, and community-acquired pneumonia) and chronic diseases were present in all groups. One coal miner (2.9%) from the group with 7-10 years of underground work experience was diagnosed with an occupational disease. The development of radiological changes in the chest organs (pulmonary fibrosis, symptoms of chronic bronchitis) was detected in the groups with an experience of up to 3 years, 3-5 years, 5-7 years, and 7-10 years in 6.4%, 9.4%, 11.1%, and 5.8% of miners, respectively. Conclusion — According to logistic regression data, underground experience of 7-10 years has led to the reduction in the levels of xanthine and uric acid in the blood, which inflicted a statistically significant effect on the development of diseases in miners. Long-term underground work yielded 8.6-fold increase in the risk of developing diseases in miners.